Analisis Strategi Pemasaran dalam Meningkatkan Keputusan Pembelian Konsumen pada Suzuya Cabang Denai - Fahriani Astuti Br Sitepu (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Each company employs its own strategies to capture market share and compete for customers through different marketing approaches. The selection of an appropriate marketing strategy and marketing mix enables a company to create, develop, and sustain the marketing of its products and services more effectively. This study is field research using a descriptive method with a deductive approach. Data were collected through both structured and unstructured interviews, as well as observations and documentation. The data were analyzed using a qualitative descriptive method. The findings indicate that the 5P marketing strategy (retail marketing mix) implemented by Suzuya Denai Branch to enhance consumers' purchasing decisions consists of product, price, promotion, people (service), and physical evidence (physical facilities). The results also reveal that the primary factors influencing consumers' purchasing decisions at Suzuya are affordable prices, quality customer service, and attractive promotional offers. However, product variety and physical facilities require further evaluation, as the supermarket should pay greater attention to improving these aspects to better meet consumer expectations.